2012
DOI: 10.1186/1477-7819-10-272
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous adenocarcinomas of the colon presenting as synchronous colocolic intussusceptions in an adult

Abstract: Intussusception is uncommon in adults. To our knowledge, synchronous colocolic intussusceptions have never been reported in the literature. Here we described the case of a 59-year-old female of synchronous colocolic intussusceptions presenting as acute abdomen that was diagnosed by CT preoperatively. Laparotomy with radical right hemicolectomy and sigmoidectomy was undertaken without reduction of the invagination due to a significant risk of associated malignancy. The final diagnosis was synchronous adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Synchronous colocolic intussusception is extremely rare and has been reported by Chen et al 4 in 2012 in association with synchronous adenocarcinoma in the proximal transverse and sigmoid colon. To the best of our knowledge, no other case report of synchronous colocolic intussusceptions has been reported in the literature and none in association with Peutz–Jeghers syndrome.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Synchronous colocolic intussusception is extremely rare and has been reported by Chen et al 4 in 2012 in association with synchronous adenocarcinoma in the proximal transverse and sigmoid colon. To the best of our knowledge, no other case report of synchronous colocolic intussusceptions has been reported in the literature and none in association with Peutz–Jeghers syndrome.…”
Section: Discussionmentioning
confidence: 95%
“… 3 CT scan may also define the location, nature of the mass and its relationship to the surrounding tissues; additionally, it may help in disease staging in patients in whom malignancy is the suspected cause of intussusceptions. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that the lead points of colonic intussusception were mostly due to villous or type 1 (protruded type; Bormann's classification type 1) tumors [ 10 , 16 – 20 ]. Chen et al reported synchronous double colocolic intussusception and that both adenocarcinomas revealed macroscopic type 1 or villous adenocarcinomas with subserosal invasion [ 21 ]. In the present case report, we also found that type 1 adenocarcinoma with subserosal invasion resulted in colonic intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare in adults, and it represents only 5% of all intussusceptions and 1-5% of all bowel obstruction cases [1,2,[4][5][6][7][8][9][10][11][12]. Unlike pediatric patients in whom it is generally idiopathic, in adults, over 90% are due to an established pathology [1,7,8]. We present a case of a patient with ileocecal intussusception secondary to a colon adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%